The Depleted Carbon Isotopic Signature of Nematodes and Harpacticoids and Their Place in Carbon Processing in Fish Farm Sediments - Grego, Mateja; Malej, Alenka; De Troch, Marleen (Frontiers in Marine Science, 2020)
Fish farm-originating organic matter can modify the processes in a benthic ecosystem. This was investigated in the sediments of the northern Adriatic Sea by δ13C signature of nematodes, harpacticoids, and sedimentary organic matter, and by pore water nutrients and bacterial composition. In a mesocosm experiment, 13C-labeled diatoms were added on top of sediment cores and 13C enrichment was measured as a proxy of diatom uptake by meiofauna. The δ13C signatures were depleted under fish farming cages compared to the reference site, as observed for sedimentary organic matter (-24.4‰ vs. -21.8‰), for nematodes (-22.5‰ vs. -17.7‰), and for harpacticoids (-25.3‰ vs. -20.8‰). The direct consumption of fish feed (-22.2‰) was not traced in meiofauna taxa. Nematodes from the farm site likely reflect a diet comprising sedimentary organic matter, as they were enriched by 2‰ relative to the sedimentary organic matter. The nematodes from the reference site were enriched by 4.2‰ relative to the sedimentary organic matter, which implies that they rely on more enriched food sources, like diatoms, which was confirmed by their uptake of 13C-labeled diatoms. The nematode assemblage incorporated more diatom 13C than harpacticoids, making them more important players in the carbon flux from diatoms to higher trophic levels at the reference site. Harpacticoids from the reference site were enriched by 1.1‰ compared to sedimentary organic matter, implying that this was their primary food source. Harpacticoids from the farm site were depleted by 0.9‰ relative to the sedimentary organic matter, indicating they are influenced by a very negative food source, potentially bacteria. Harpacticoids from both the cage and reference sites consumed 13C-labeled diatoms, which implies their diet might span a broad δ13C range, from bacteria to diatoms. Pore water nutrients with high DIC, PO43-, and NH4+ concentration indicated an elevated microbial degradation of organic compounds under the fish farm. DGGE analysis showed a 70% similarity between sediment bacteria communities from the fish farm and reference site. The study demonstrated that fish farm-originating organic matter enters the meiofauna food chain, and that nematodes and harpacticoids use different food sources under the fish farm and at the reference site.